Muscle fatigue assessment by mechanomyography and muscle oxygenation during electrically-evoked wrist extension exercise / Nurul Salwani Mohamad Saadon - Nurul Salwani, Mohamad Saadon (2019)
Repetitive electrically-evoked muscle contraction leads to accelerated muscle fatigue. This study assessed electrically-evoked fatiguing muscle with changes to mechanomyography root mean square percentage (%RMS-MMG) and tissue saturation index (%TSI-NIRS) in extensor carpi radialis (ECR) muscle in able-bodied (AB) and in participants with spinal cord injury (SCI). Due to the limited research from previous studies, it is important to investigate the relationship in AB participants first to understand the natural behavior of the muscle mechanically and physiologically as AB has more power in their muscle to perform exercise compared to SCI participants. AB and SCI performed repetitive electrical-evoked wrist extension to fatigue and results were analysed pre- and post-fatigue, i.e. 50% power output (%PO) drop. Responses of %PO, %TSI-NIRS and %RMS-MMG were correlated while the relationship between %RMS-MMG and %TSI-NIRS were investigated using linear regression. Forty AB (N=40) volunteered in the study. %TSI-NIRS were negatively correlated pre- and post-fatigue with declining %PO as the ability of the muscle to take up oxygen became limited due to fatigued muscle. The %RMS-MMG behaved in two different patterns post-fatigue against declining %PO whereby; (i) group (A) showed positive correlation (%RMS-MMG decreased) throughout the session and (ii) group (B) demonstrated negative correlation (%RMS-MMG increased) with declining %PO until the end of the session. Regression analysis showed %TSI-NIRS was inversely proportional to %RMS-MMG in group A and proportional in group B during post-fatigue. Small gradients in both groups suggested that %TSI-NIRS was not sensitive to the changes in %RMS and they were mutually iv exclusive. As for SCI, seven SCI participants (N=7) were recruited and %TSI-NIRS was positively correlated with %PO pre-fatigue. At post-fatigue, %TSI-NIRS negatively correlated with declining %PO as the ability of the muscle to take up oxygen became limited due to fatigued muscle. The %RMS-MMG behaved the same way during pre- and post-fatigue against declining %PO whereby both showed positive correlation (%RMS-MMG decreased) throughout the session. Regression analysis showed %TSI-NIRS was proportional pre-fatigue and inversely proportional to %RMS-MMG during post-fatigue. As big gradient was observed from the regression during post-fatigue, it is suggested that changes in %TSI-NIRS were sensitive enough to the changes in %RMS-MMG. Most correlation and regression for both AB and SCI changed significantly post-fatigue indicating that after fatigue, the condition of muscle had changed mechanically and physiologically.